Beyond the K Line - A Commentary on “The Role of K-Line and Canal-Occupying Ratio in Surgical Outcomes for Multilevel Cervical Ossification of the Posterior Longitudinal Ligament: A Retrospective Multicenter Study” - Russo, Fabrizio; Vadalà, Gianluca; Denaro, Vincenzo (Neurospine, 2025)
KCI Citation Count: 0